The Role of Reliable Absorbents Based on Local Raw Materials for Natural Gas Purification - Xusnitdinovna , Kuchkarova Noila; o‘g‘li, Egamberdiyev Jonibek Davron; qizi, Darxanova Sevinch Abduvoxid; o‘g‘li, Masharipov Og‘abek Aminboy; qizi , Qahramonova Sevinch O‘tkir (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article highlights the role of the gas industry in the economy of our Republic, classification and description of methods for natural gas purification using local raw materials.